Evaluation of simulated external root resorptions with digital radiography and digital subtraction radiography - Ono, Evelise [UNESP]; Medici Filho, Edmundo [UNESP]; Leite, Horacio Faig [UNESP]; Oshiro Tanaka, Jefferson Luis [UNESP]; Leonelli de Moraes, Mari Eli [UNESP]; De Melo Castilho, Julio Cezar [UNESP] (Mosby-elsevier, 2011)
Introduction: Root resorption can cause damage in orthodontic patients. Digital subtraction radiography (DSR) is a useful resource for the detection of mineral losses. The purpose of this study was to compare the efficacy of digital radiography (DR) and DSR in detecting simulated external root resorption. Examiner agreement between the 2 techniques was also evaluated. Methods: Root resorptions of various sizes were simulated on the apical and lingual aspects of 49 teeth from 9 dry human mandibles. The teeth were radiographed in standardized conditions. The radiographs were registered with Regeemy Image Registration and Mosaicking (version 0.2.43-RCB, DPI-INPE, Sao Jose dos Campos, São Paulo, Brazil) and subtracted with Image Tool (University of Texas Health Science Center at San Antonio). The subtracted images and the digital radiographs were evaluated by 3 oral radiologists. Results: No statistically significant differences were found for the methods in the detection of apical root resorptions, independently from lesion size, and of lingual resorptions of 1.2 mm or greater. DSR was significantly better than DR for detection of lingual resorptions up to 1 mm. Resorptions less than 0.5 mm were not precisely detected by either method. DSR provided better intraexaminer and interexaminer agreement than did DR. Conclusions: Both methods are precise for detection of apical root resorptions as small as 0.5 mm and lingual resorptions of 1 mm or more. However, DSR frequently performed better than did DR. (Am J Orthod Dentofacial Orthop 2011;139:324-33)